2018
DOI: 10.12669/pjms.345.15574
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of laparoscopic surgery combined with triptorelin acetate in patients with endometriosis and infertility

Abstract: Objective:To investigate the effects of laparoscopic surgery combined with triptorelin acetate, gestrinone and mifepristone on pregnancy rate, pregnancy outcome, long-term recurrence and adverse reactions in patients with endometriosis (EMT) complicated with infertility.Methods:In this study, 150 patients with EMT and infertility were selected and randomly divided into triptorelin group (group A), gestrinone group (group B) and mifepristone group (group C), with 50 people in each group. Treatment was with gona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
11
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 16 publications
3
11
2
Order By: Relevance
“…Both formulations of triptorelin had a beneficial treatment effect, demonstrated by the proportion of patients chemically castrated after treatment and reduction in endometriosis-associated pelvic pain, which was similar between groups and consistent with numerous previous studies of triptorelin in the management of endometriosis [ 13 , 24 26 ]. In addition, the present findings are consistent with a previous phase 2, prospective, randomized, open-label study comparing the 3-month formulation and 1-month formulation of triptorelin in 146 European women with endometriosis [ 19 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Both formulations of triptorelin had a beneficial treatment effect, demonstrated by the proportion of patients chemically castrated after treatment and reduction in endometriosis-associated pelvic pain, which was similar between groups and consistent with numerous previous studies of triptorelin in the management of endometriosis [ 13 , 24 26 ]. In addition, the present findings are consistent with a previous phase 2, prospective, randomized, open-label study comparing the 3-month formulation and 1-month formulation of triptorelin in 146 European women with endometriosis [ 19 ].…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with previous studies, the most common AEs in patients treated with triptorelin were hot flashes and night sweats [14,27]. The safety profiles of triptorelin pamoate PR 3-month and triptorelin acetate PR 1-month were also consistent with previous studies of triptorelin acetate PR 1-month, which reported that the formulation was generally well tolerated and did not result in serious AEs [24,26].…”
Section: Discussionsupporting
confidence: 88%
“…26 However, as the study did not directly capture how many women tried to become pregnant during the 24 months follow-up, the interpretation of this observation is unclear. Furthermore, the present 24-month pregnancy rate for infertile patients was substantially lower than the 24-month pregnancy rate of 80% observed in infertile patients treated with triptorelin in the randomized controlled trial by Xue et al 19 A possible reason for this difference is the older age of patients in this study compared with the study by Xue et al (mean age, 33.4 vs. 26.7 years), as the problem of infertility is greater and the planning of pregnancy less common in older patients.…”
Section: Discussioncontrasting
confidence: 82%
“…The most common adverse effects in patients treated with triptorelin were menopause symptoms (hot flash/flush, sweat/night sweat) in agreement with results from previous studies. 15,16,19,29…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation